First record of the rare Dyckia racemosa Baker (Bromeliaceae) in Maranhão state (northeastern Brazil), with an update on the species description, geographic distribution, and conservation status - Guarçoni, Elidio A.e.; Bastian, Regis E.; Silva, Eduardo O.; Ferreira, Alessandro W. C. (Phytotaxa, 2018)
Dyckia racemosa is a Bromeliaceae species known from only three collections near Serra Geral, Central Brazil. In this study, the area of occurrence of the species is reported to extend to a Cerrado area in Maranhão state, northeastern Brazil. Digital collections from Brazilian and international herbaria were consulted. The species original description is complemented herein with illustrations and information on the species phenology, ecology, and conservation status. The discovery of D. racemosa in Maranhão demonstrates the importance of floristic studies and the need for further research of this nature in that Brazilian state.